Photodynamic therapy of experimental rat sarcoma M-1 with photosensitizer borated chlorine - J. S. Osipchuk; M. A. Kaplan; V. V. Drozhzhina; V. A. Polyakova (Biomedical Photonics, 2015)
On model of experimental sarcoma М-1 the efficiency of photodynamic therapy (PDT) has been studied with using as photosensitizer boronated chlorine. The doses of the last was 5 mg/kg of mass of an animal. A laser irradiation was spent at densities of energy 150 J/cm2 and power 0,25 V/cm2. Effect PDT was estimated by percent of animals with full regress of the tumor, to quantity of relapses, and in situation of the tumor growth by dynamic of coefficient of absolute it increase. Experiences have been lead on 6 pubertal rats. As the control not treated animals with tumor served. Researches have shown, that efficiency of PDT depends on a dose boronated chlorine and conditions of a laser irradiation.